Actual Cost Price dan Penetapan Margin Murabahah Dalam Perspektif Syariah (Studi Kasus Pada Bank Syariah Indonesia (BSI) Makassar) - Muthahharah Syahidah; Mursalim Mursalim; Tenriwaru Tenriwaru (Journal on Education, 2023)
The purpose of this research is to find out and analyze the actual cost pricing mechanism for determining murabaha, to find out and analyze the determination of murabaha margins, and to find out and analyze the implementation of actual cost pricing and murabahah margins carried out by Indonesian Sharia Bank, Makassar from a sharia perspective. To apply these objectives, data collection techniques were used through interviews, observation and documentation, with data analysis techniques using actual cost pricing analysis, murabahah margin determination analysis and comparison analysis of actual cost pricing and murabaha margins with a sharia perspective. The results of the study show that the actual cost price, namely the cost price in a sale and purchase transaction, is an agreement for Indonesian Islamic banks, Makassar in determining the selling price of murabahah equal to the cost price (buying) plus a profit margin. Then the determination of the profit margin/mark-up in financing under a murabaha contract is not carried out at the BSI branch office, but the authority to determine the profit margin/mark-up percentage is the head office and at the BSI Branch office only carry out according to the regulations including the system and every profit margin/mark up by BSI Syariah, the Makassar branch is only set for one transaction and payments are made in installments according to the financing implementation period agreed by the customer. Based on the results of the analysis regarding the actual cost pricing and margin/mark up in financing under a murabaha contract, it can be said that BSI, Makassar branch has carried out according to sharia principles. This is in accordance with the data analysis where in the implementation of the research it was found that there were no elements of usury, maisir, garar, haram and unjust.